State-space based time integration method for structural systems involving multiple nonviscous damping models. (15th July 2016) - Ding, Zhe; Li, Li; Hu, Yujin; Li, Xiaobai; Deng, Weiming
Highlights: A direct time integration method for nonviscously damped system is proposed. An extended state-space method is developed. A general nonviscously damped model is proposed. The method is applicable to systems involving multiple damping models. Two examples are given to show the accuracy and efficiency of the method. Abstract: Engineering structures are often assembled by subsections with various levels of energy dissipation, which lead to great difficulties in analyzing. In this paper, a direct time integration method is proposed to solve the dynamic responses of structural systems involving multiple nonviscous damping models. Based on a general non-viscously damped model, an extended state-space scheme for the damped system is derived. Then, an implicit time integration method using linear approximations is developed built on the extended state-space formalism. The stability and efficiency of the method are discussed by theoretical and numerical analyses. The method is illustrated by two examples.